Exploring Blended Learning on the Students’ Academic Achievement in A Pragmatics Course - Ahmad Wahyu Saputra; Andi Anto Patak; Seny Luhriyani Sunusi (Journal of Excellence in English Language Education, 2026)
The use of blended learning has become increasingly important in higher education, particularly in language courses that require contextual understanding. This study investigates the implementation of blended learning in the Pragmatics course at the Business English Communication (BEC) program and examines its impact on students’ learning experience, engagement, and academic achievement. A qualitative descriptive approach was employed, involving six BEC students who participated in semi-structured interviews. The data were analyzed using reflexive thematic analysis. The findings reveal that blended learning is implemented through a combination of face-to-face instruction and online activities, which provides learning flexibility and supports students’ understanding of pragmatic concepts. Most students reported positive learning experiences, increased engagement, and improvements in academic performance and pragmatic skills, although some challenges related to online interaction were identified. In conclusion, blended learning contributes positively to the learning process and academic achievement of BEC students in the Pragmatics course when effectively integrated with both online and face-to-face components.